2020
DOI: 10.1002/phar.2404
|View full text |Cite
|
Sign up to set email alerts
|

Akathisia and Newer Second‐Generation Antipsychotic Drugs: A Review of Current Evidence

Abstract: Akathisia continues to present a significant challenge in clinical practice. As a class, so-called atypical, or second-generation, antipsychotics (SGAs) are the mainstay of treatment for schizophrenia and are commonly used to treat mood disorders. These medications have traditionally been distinguished from first-generation antipsychotics by their lowered risk of extrapyramidal side effects (EPS) such as dystonia, dyskinesia, akathisia, and pseudoparkinsonism. However, the occurrence of EPS, particularly akath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 103 publications
2
9
0
1
Order By: Relevance
“…30,31 In addition to schizophrenia and nasopharyngitis, akathisia and nausea were also among the more common adverse events during the current 12-week extension study, though occurring at a low overall incidence (akathisia at 6.6% of patients was the most common TEAE). Although study designs differ, the incidence of akathisia for some antipsychotic drugs in patients with schizophrenia has been reported 32 to be 3-13% across various studies, and the current result is also within that range. The lack of noticeable effects on weight, BMI, metabolic parameters, prolactin, and ECG parameters in the current study is consistent with previous safety findings, 30,31 and the double-blind study that preceded the extension study reported here.…”
Section: Discussionsupporting
confidence: 50%
“…30,31 In addition to schizophrenia and nasopharyngitis, akathisia and nausea were also among the more common adverse events during the current 12-week extension study, though occurring at a low overall incidence (akathisia at 6.6% of patients was the most common TEAE). Although study designs differ, the incidence of akathisia for some antipsychotic drugs in patients with schizophrenia has been reported 32 to be 3-13% across various studies, and the current result is also within that range. The lack of noticeable effects on weight, BMI, metabolic parameters, prolactin, and ECG parameters in the current study is consistent with previous safety findings, 30,31 and the double-blind study that preceded the extension study reported here.…”
Section: Discussionsupporting
confidence: 50%
“…[11][12][13][14] Akathisia is one of the most frequently occurring movement disorders associated with antipsychotic agents, although the propensity for its occurrence differs by pharmacologic profile and receptorbinding affinities; all antipsychotics may cause some degree of akathisia, with lower rates generally noted for second-generation agents versus first-generation agents. 15 Cariprazine is a dopamine D 3 /D 2 receptor partial agonist that is approved by the European Medicines Agency (EMA) and by the United States (US) Food and Drug Administration (FDA) for the treatment of schizophrenia (1.5-6 mg/d); it is additionally approved in the US for manic and mixed episodes associated with bipolar I disorder (3-6 mg/d), and for bipolar depression (1.5 or 3 mg/d). 16 Cariprazine differs from all other atypical antipsychotics in having a greater affinity for the D 3 receptor than does dopamine itself, thereby exhibiting a functional D 3 partial agonism in the human brain 17 that other antipsychotics, such as aripiprazole, risperidone, and olanzapine, fail to exhibit.…”
Section: Introductionmentioning
confidence: 99%
“… 55 58 The relative “EPS advantage” of second-generation agents is touted as producing multiple clinical benefits, 59 , 60 but movement side effects can still occur in second-generation agents despite lower D 2 receptor occupancy. 5 , 24 , 34 , 61 , 62 …”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57][58] The relative "EPS advantage" of second-generation agents is touted as producing multiple clinical benefits, 59,60 but movement side effects can still occur in secondgeneration agents despite lower D 2 receptor occupancy. 5,24,34,61,62 The risk of akathisia, for instance, may be comparable or even greater in second-generation agents. 52 Akathisia does not correspond well with other types of EPS in terms of symptom severity and treatments, suggesting that there are other important mechanisms underlying its development.…”
Section: Current Understanding Of Pathophysiologymentioning
confidence: 99%